Effectiveness and cost-effectiveness of referral to a commercial open group behavioural weight management programme in adults with overweight and obesity: 5-year follow-up of the WRAP randomised controlled trial. (October 2022) - Ahern, Amy L; Breeze, Penny; Fusco, Francesco; Sharp, Stephen J; Islam, Nazrul; Wheeler, Graham M; Hill, Andrew J; Hughes, Carly A; Duschinsky, Robbie; Thomas, Chloe; Bates, Sarah; Woolston, Jenny; et al.
Summary: Background: There is evidence that commercially available behavioural weight management programmes can lead to short-term weight loss and reductions in glycaemia. Here, we aimed to provide the 5-year impact and cost-effectiveness of these interventions compared with a brief intervention. Methods: WRAP was a non-blinded, parallel-group randomised controlled trial (RCT). We recruited from primary care practices in England and randomly assigned participants to one of three interventions (brief intervention, 12-week open-group behavioural programme [WW, formerly Weight Watchers], or a 52-week open-group WW behavioural programme) in an uneven (2:5:5) allocation. Participants were followed up 5 years after randomisation using data from measurement visits at primary care practices or a research centre, review of primary care electronic medical notes, and self-report questionnaires. The primary outcome was change in weight at 5 years follow-up, assessed using analysis of covariance. We also estimated cost-effectiveness of the intervention. This study is registered at Current Controlled Trials, ISRCTN64986150. Findings: Between Oct 18, 2012, and Feb 10, 2014, we recruited 1269 eligible participants (two participants were randomly assigned but not eligible and therefore excluded) and 1040 (82%) consented to be approached about additional follow-up and to have their medical notes reviewed at 5 years. The primary outcome (weight) was ascertained for 871 (69%) of 1267 eligible participants. Mean duration of follow-up was 5·1 (SD 0·3) years. Mean weight change from baseline to 5 years was −0·46 (SD 8·31) kg in the brief intervention group, −1·95 (9·55) kg in the 12-week programme group, and −2·67 (9·81) kg in the 52-week programme. The adjusted difference in weight change was –1·76 (95% CI –3·68 to 0·17) kg between the 52-week programme and the brief intervention; –0·80 (–2·13 to 0·54) kg between the 52-week and the 12-week programme; and –0·96 (–2·90 to 0·97) kg between the 12-week programme and the brief intervention. During the trial, the 12-week programme incurred the lowest cost and produced the highest quality-adjusted life-years (QALY). Simulations beyond 5 years suggested that the 52-week programme would deliver the highest QALYs at the lowest cost and would be the most cost-effective. No participants reported adverse events related to the intervention. Interpretation: Although the difference in weight change between groups was not statistically significant, some weight loss was maintained at 5 years after an open-group behavioural weight management programme. Health economic modelling suggests that this could have important implications to reduce the incidence of weight-related disease and these interventions might be cost-saving. Funding: The UK National Institute for Health and Care Research Programme Grants for Applied Research and the Medical Research Council.